Organizing for entrepreneurship: Field-experimental evidence on the performance effects of autonomy in choosing project teams and ideas - Viktoria Boss; Christoph Ihl; Linus Dahlander; Rajshri Jayaraman (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Organizations constantly strive to unleash their entrepreneurial potential to keep up with market and technology changes. To this end, they engage employees in practices like corporate crowdsourcing, incubators, accelerators or hackathons. These organizational practices emulate independent "green-field" entrepreneurship by relinquishing hierarchical control and granting employees autonomy in the choices of how to conduct work. We aim to shed light on two such choices that are fundamental in differentiating hierarchical from entrepreneurial modes of organizing work: (1) choosing projects ideas to work on and (2) choosing project teams to work with. Both of these choices are typically pre-determined in hierarchies and self-determined in entrepreneurship. We run a field experiment in an entrepreneurship course carefully designed to disentangle the separate and joint effects of granting autonomy in both choosing teams and choosing ideas compared to a pre-determined base case. Our results show that high autonomy in choosing implies a trade-off between personal satisfaction and objective performance. Self-determined choices along both dimensions promote subjective well-being in a complementary way, but their joint performance impact is diminishing. After ruling out alternative explanations related to differing project qualities and homophilic team choices, the detrimental performance impact of too much choice seems to be related to the implied cognitive burden and overconfidence.
Keywords: L23; L26; M5; 330; teams; ideation; entrepreneurial performance; field experiment